(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Financial inclusion has been a key priority for India. Since finance serves as a catalyst for economic development, the relevance of financial inclusion stretches beyond the realm of finance to socioeconomic development. This paper main objective is to examine the relationship between financial inclusion and rural development through micro finance in India and to analyze the performance of micro finance- SHGs Bank Linkage Programme. In India, micro-Finance scene is dominated by Self Help Groups (SHGs) - Banks linkage Programme, aimed at providing a cost effective mechanism for providing financial services to the unreached poor. The focus of thissector must be on Digital Microfinance. Keeping in view the need to increase transparency, address customer-centric issues and safeguard the interests of low-income customers, microfinance lenders must put the interests of their clients first and implement the Code for Responsible Lending and the Code of Conduct in both letter and spirit. Redressing consumer complaints quickly and effectively it should be on top of the agenda for MFIs and the Self- Regulatory Organizations (SROs). It is concluded that the Financial Inclusion plays a vital role in providing economic opportunity and improves the living standard for inclusive growth. Micro-Finance is emerging as a powerful instrument for poverty alleviation in the new economy